For the Children, Perfect Instruction : Studies in Honor of Hans-Martin Schenke on the Occasion of the Berliner Arbeitskreis für koptisch-gnostische Schriften's Thirtieth Year - Bethge, Hans-Gebhard,; Emmel, Stephen,; King, Karen,; Schletterer, Imke, (Nag Hammadi and Manichaean Studies ;, 2002)
Prof. Dr. Hans-Martin Schenke, internationally renowned New Testament scholar and pioneer researcher in Gnosticism as it became brilliantly illuminated by the publication of the Nag Hammadi Codices, organized a small group of students and colleagues in "East Berlin" in the early 1970s to investigate the difficult new primary sources from the "Coptic Gnostic Library" discovered in Upper Egypt in 1945. This group, the "Berliner Arbeitskreis für Koptisch-Gnostische Schriften," published its first results in 1972, and Prof. Schenke and the Arbeitskreis have been at the forefront of Nag Hammadi studies ever since. The present volume is a collection of twenty-seven studies by colleagues, students, and friends of Prof. Schenke in honor of his many contributions to the study of Gnosticism and related religious phenomena in Antiquity, Coptic language and literature, and the New Testament. The book also includes an extensive bibliography of Prof. Schenke's own publications, whose breadth and insightfulness are appropriately mirrored in the variety of contributions to this rich volume.